Regulatory Gaps and the Emerging Risk of Electric Vehicle Battery Fires in Indonesia - Rudijanto, Maria Natasha (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The development of electric vehicles (EVs) in Indonesia is experiencing a positive trajectory; however, the risk of battery-related fires remains a significant challenge that is not yet comprehensively addressed within the national regulatory framework. This study aims to assess the effectiveness of Indonesia’s legal framework in mitigating the risk of EV battery fires by analyzing regulatory implementation, technical challenges, and the extent of consumer legal protection. A normative legal approach is employed, focusing on the analysis of national laws and regulations alongside relevant international standards. The findings reveal that existing national regulations remain fragmented and insufficiently responsive to the rapid advancements in battery technology, particularly concerning safety testing protocols and thermal risk management. When compared to international standards such as UNECE Regulation No. 100 and UL 2580, Indonesia’s legal framework demonstrates a substantial need for harmonization. In conclusion, the study highlights the urgent need for adaptive, integrated, and risk-based regulatory reforms to ensure consumer safety while simultaneously enhancing the competitiveness of Indonesia’s electric vehicle industry in both domestic and international markets.